Characterization of CR-Lightlike-Warped Product of Indefinite Kaehler Manifolds. (1st December 2011) - Rani, Rachna; Kumar, Rakesh; Nagaich, R. K.
Abstract : In this paper, we prove that there does not exist a warped product CR-lightlike submanifold in the form M = N ⊥ × λ N T other than CR-lightlike product in an indefinite Kaehler manifold. We also obtain some characterizations for a CR-lightlike submanifold to be locally a CR-lightlike warped product.